Housing, Home and Children's Socio-Emotional Health: Conceptual Ideas and Empirical Evidence from a South African Pilot Study. Issue 5 (20th October 2022) - Gbadegesin, Frances; Marais, Lochner; Cloete, Jan; Rani, Kholisa; Lenka, Molefi; Serekoane, Motsaathabe; Boivin, Michael; Shohet, Cilly; Givon, Deborah; Sharp, Carla
ABSTRACT: The literature linking home and housing with the socio-emotional health of children focuses primarily on the physical attributes of housing. We conducted a pilot study to measure physical and socio-emotional attributes of housing for a sample of 69 children from a low-resource setting in South Africa. We used the Home Observation for Measurement of the Environment (HOME) inventory and the Strengths and Difficulties Questionnaire (SDQ). We analysed the data using descriptive and inferential methods. Our preliminary evidence from the descriptive methods shows that the children's socio-emotional health had a statistically significant correlation with six of the subscales in the HOME inventory but with only two of the physical attributes of their housing. We conclude that studies of the relationship between home and children's socio-emotional health should pay more attention to the concept of home and how it has been operationalized through the HOME inventory.